Effect of prednisolone on language function in children with autistic spectrum disorder: a randomized clinical trial - Adriana Rocha Brito; Giselle de Paula Teixeira Vairo; Ana Paula Botelho Henriques Dias; Beni Olej; Osvaldo José Moreira Nascimento; Marcio Moacyr Vasconcelos (Elsevier, 2021)
Objective: To describe the effect of prednisolone on language in children with autism spectrum disorder. This study is based upon two hypotheses: autism etiology may be closely related to neuroinflammation; and, an effective treatment should restore the individual's language skills. Method: This is a prospective, double-blinded, randomized, placebo-controlled clinical trial, carried out in a federal university hospital. The initial patient sample consisted of 40 subjects, which were randomized into two parallel groups. Inclusion criteria were: male gender, 3-7 years of age, and meeting the Diagnostic and Statistical Manual of Mental Disorders - 4th edition (DSM-IV) diagnostic criteria. The final sample consisted of 38 patients, of whom 20 were randomized to the placebo group and 18 to the active group. The latter received prednisolone for 24 weeks, at an initial dose of 1 mg/kg/day and a tapering dose from the ninth week onward. Language was measured on four occasions over a 12-month period by applying two Brazilian tools: the Language Development Assessment (ADL) and the Child Language Test in Phonology, Vocabulary, Fluency, and Pragmatics (ABFW). Results: The side effects were mild: two patients had hypertension, five had hyperglycemia, and two had varicella. Prednisolone increased the global ADL score in children younger than 5 years of age who had developmental regression (p = 0.0057). The ABFW's total of communicative acts also responded favorably in those participants with regression (p = 0.054). The ABFW's total of vocal acts showed the most significant results, especially in children younger than 5 years (p = 0.004, power = 0.913). Conclusions: The benefit of prednisolone for language scores was more evident in participants who were younger than five years, with a history of developmental regression, but the trial's low dose may have limited this benefit. The observed side effects do not contraindicate corticosteroid use in autism.